Odpowiedzi

Najlepsza Odpowiedź!
2010-01-14T21:12:42+01:00
A) (-13) * (-2) *1/2 * (-5)=
26 * 1/2 * -5 =
13 * -5=
-65

b) (-1/3) * 1 1/5 * (-12) * (-1/6)=
-2/5 * -12 * -1/6=
4,8 * -1/6=
-4/5

c) (-100) * 3,125 * (-1 1/2) * (- 1/25)=
-312,5 * -1,5 * -0,4=
468,75 * -0,4=
-187,5

d) (-0,8) * (-500)=400

e) -4,2 * (-5)=21

f) -20 *17 = -340
2010-01-14T21:14:19+01:00
A) (-13) * (-2) *1/2 * (-5)= (-13) * (-1)*(-5)=13*(-5)=-65
b) (-1/3) * 1 1/5 * (-12) * (-1/6)=(-1/3)*6/5*2=(-2/5)*2=-4/5
c) (-100) * 3,125 * (-1 1/2) * (- 1/25)=(312,5)*0.06=-18,75
d) (-0,8) * (-500)=400
e) -4,2 * (-5)=21
f) -20 *17 =-340